2018
DOI: 10.1038/s41467-017-02634-6
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal phase transition between two-dimensional high-density liquid crystal and low-density crystalline solid phases

Abstract: Some two-dimensional liquid systems are theoretically predicted to have an anomalous phase transition due to unique intermolecular interactions, for example the first-order transition between two-dimensional high-density water and low-density amorphous ice. However, it has never been experimentally observed, to the best of our knowledge. Here we report an entropy-driven phase transition between a high-density liquid crystal and low-density crystalline solid, directly observed by scanning tunneling microscope i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 46 publications
1
6
0
Order By: Relevance
“…Considering that there is an electric field between the STM tip and sample, and the electric field-induced structural phase transition has been observed in other systems, we studied the effect of the electric field on the phase transition by repeatedly scanning the same area to reveal the time-dependent topology evolution of sample 2. Figure shows the topography image scanned under the same bias voltage, 1 V, where there are two main regions covered by the β phase coated in green and yellow, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Considering that there is an electric field between the STM tip and sample, and the electric field-induced structural phase transition has been observed in other systems, we studied the effect of the electric field on the phase transition by repeatedly scanning the same area to reveal the time-dependent topology evolution of sample 2. Figure shows the topography image scanned under the same bias voltage, 1 V, where there are two main regions covered by the β phase coated in green and yellow, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…30 They also showed that free-standing gallenene can be dynamically stabilized upon the application of biaxial strain. Surface functionalization is an alternative approach to strain that can improve the stability of 2D materials and for tuning their structural, 31,32 electronic, 33,34 and magnetic 35 properties. Generally, hydrogenation is utilized experimentally for surface functionalization because it is a simple and versatile method.…”
Section: Introductionmentioning
confidence: 99%
“…Saturated adsorption of achiral CO molecules on various substrates have been observed to form stable phases consisting of clusters due to spontaneous condensation at low temperature. For examples, hexamer and heptamer structures have been suggested on the (111) plane of bulk α-CO [33][34][35] , as well as a CO adlayer on graphite 36 , Ag(111) 37 and Cu(111) 38 . Other chiral systems of clusters induced by symmetrybreaking adsorption process have also been reported, such as water adsorption on Ag(111) 39 and NaCl(001) 40 .…”
Section: Discussionmentioning
confidence: 99%